1990
DOI: 10.1177/104239159000200402
|View full text |Cite
|
Sign up to set email alerts
|

A Method To Predict the Fire Resistance of Circular Concrete Filled Hollow Steel Columns

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 5 publications
(1 reference statement)
0
59
0
1
Order By: Relevance
“…For concrete, the difference between different models can be quite large. Since this study uses the test results of Lie and Chabot (1992), the concrete model proposed by Lie and Chabot (1990) was adopted. It should be pointed out that the concrete model of Lie and' Chabot (1990) gives much higher strength retention factor than Eurocode 4 Part 1.2 (CEN 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For concrete, the difference between different models can be quite large. Since this study uses the test results of Lie and Chabot (1992), the concrete model proposed by Lie and Chabot (1990) was adopted. It should be pointed out that the concrete model of Lie and' Chabot (1990) gives much higher strength retention factor than Eurocode 4 Part 1.2 (CEN 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The fire resistance of the column is the standard fire exposure time at which the column load carrying capacity decreases to the level of -tlie appliea]oi!d. These calculations may be performed at different levels of complexity ranging from detailed finite element analysis (Kodur and Lie 1996a, Lie and Chabot 1990, Wang and Moore 1995, to give a complete history for the stress, strain and deflection in the column, to a design procedure in which only the column load carrying セ ー 。 」 ゥ エ is calculated (CEN 1994). Some of the recent studies (Lie and Kodur 1996) have focused on developing simple design equations for evaluating the fire resistance of concrete filled steel columns.…”
Section: Introductionmentioning
confidence: 99%
“…For the mechanical model of CFSTRC columns, solid elements (C3D8) were used for the endplates and steel pipe, reinforced concrete, and core concrete, whereas truss elements (T3D2) were used for the steel bars. The present study adopted the steel stress-strain models presented by Lie and Chabot (1990) as well as the thermal expansion models for steel and concrete proposed in Lie (1994). The compressed stress-strain relationship models of the core concrete and reinforced concrete under fire were acquired from Han (2007) and Lie (1994), respectively.…”
Section: Finite Element Analysis Modelmentioning
confidence: 99%
“…Research on the fire resistance of HSS columns filled with plain concrete (Lie and Chabot 1990) and with bar-reinforced concrete (Lie and Irwin 1995) was previously completed. The results showed that reductions in the loads on the columns were necessary to obtain reproducible and predictable fire resistances if the columns were filled with plain concrete.…”
Section: Introductionmentioning
confidence: 99%